Extensions of Hermite-Hadamard type inequality for co-ordinated (alpha,m)-convex functions - Nik Muhammad Farhan Hakim Nik Badrul Alam,; Alawiah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this paper, the classes of (,m)  convex functions in real and complex co-ordinated space have been introduced. Some new Hermite-Hadamard type inequalities have been obtained for these classes of functions.